Antinociceptive evaluation of conventional anticonvulsant with conventional analgesics on pain model of albino rats and mice - Agarwal, Ruchika; Kansal, Saurabh (International Journal of Research in Medical Sciences, 2018)
Background: Pain is one of the most common presentations of any disorder and needs immediate and appropriate attention of the treating physician. As pain syndrome involves a variety of etiopathogenesis and temporal domains, management of pain as such requires consideration of many factors that may dictate appropriate therapeutic management. Carabmazepine is an established drug for trigeminal neuralgia while Gabapentin has been tried in postoperative pain but its effectiveness per se and when compared to conventional analgesics needs to be evaluated. Methods: The present study was planned to study the analgesic effects of Gabapentin in various pain models like writhing and formalin test and to compare it with conventional analgesics like Diclofenac sodium and Tramadol in various acute pain models. Results: This study has been carried out in department of Pharmacology, HIMS, Dehradun, for evaluation of Gabapentin for its antinociceptive effect in rats and mice. In the writhing test, a reduction in number of writhes, though insignificant, was found in the Gabapentin pre-treatment group. However, in the first phase of Formalin test which is characterized by licking and biting, Gabapentin produced no significant effect in comparison to control values. In the second phase of leg raising (LR), all three drugs, i.e. Gabapentin and the two positive controls i.e. diclofenac and tramadol produced significant decrease (p< 0.05) in episodes when compared to the control group. Conclusions: Hence the result conclude that Gabapentin could be an effective analgesic drug in visceral and chronic pain in humans but not in acute pain as first phase of formalin test is model of acute and second phase denote chronic pain while writhing test is a model of visceral pain.